2 Kajak-Fahrer in der Bucht von Nain : [ca. 1901] - Schmitt, Christian, 1868-1933. (2001)
Black and white photograph of two Inuit kayakers in Unity Bay, circa 1901. Black and white photograph of two Inuit kayakers in Unity Bay, circa 1901.